2014
DOI: 10.1177/0971333613516229
|View full text |Cite
|
Sign up to set email alerts
|

The Meanings Jamaicans Associate with Corporal Punishment

Abstract: This study examined the meanings Jamaicans associate with corporal punishment and its perceived effects on children, caregivers’/parents’ relationship with children and in a broader sense, Jamaican culture. A total of 183 readers’ comments on 13 articles that focused on corporal punishment—published in a prominent Jamaican online newspaper—were qualitatively analysed. The results indicated that not all Jamaicans engage in or embrace the use of corporal punishment. There is a clear divide between Jamaican indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Participants who attended the parenting workshop were keen to discuss alternate strategies to corporal punishment, which is still a popular method of punishment (Burke and Kuczynski, 2018). Many Jamaican parents struggle with effective and appropriate parenting (Burke and Sutherland, 2014; United Nations International Children’s Emergency Fund [UNICEF], 2018) in a society with chronic levels of poverty and violence (Arthur and Whitley, 2015). Of consideration as well is that attendees at the workshop on Workplace Wellness were recruited from organisations and companies within the private sector which typically offer Employee Assistance Programmes (EAP).…”
Section: Discussionmentioning
confidence: 99%
“…Participants who attended the parenting workshop were keen to discuss alternate strategies to corporal punishment, which is still a popular method of punishment (Burke and Kuczynski, 2018). Many Jamaican parents struggle with effective and appropriate parenting (Burke and Sutherland, 2014; United Nations International Children’s Emergency Fund [UNICEF], 2018) in a society with chronic levels of poverty and violence (Arthur and Whitley, 2015). Of consideration as well is that attendees at the workshop on Workplace Wellness were recruited from organisations and companies within the private sector which typically offer Employee Assistance Programmes (EAP).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are also consistent with studies elsewhere that found that lower social class families are more likely to use psychological control to reduce misbehavior (Hoff-Ginsberg and Tardif, 1995; Chen et al, 2015). The use of mostly power assertive strategies among lower class families may be attributed to a lack of knowledge to alternative options (Burke and Sutherland, 2014), or they may experience more economic challenges that reduce their patience level compared to middle class families.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, research on children’s socialization in the Jamaican family context has predominantly taken a traditional unilateral or parent-centered approach with an exclusive emphasis on how parents influence children through their discipline practices (Kuczynski, 2003). For example, although there have been some reports of authoritative parenting styles (Lipps et al, 2012), most studies suggest that Jamaican parents have been found to have an authoritarian parenting style, characterized by values that favor strict obedience from children and harsh, punitive discipline (UNICEF, 2010; Burke and Sutherland, 2014). The authoritarian style has been attributed to historical influences including slavery, colonialism, and conservative Christian religion (Barrow, 2001; Bush, 2010; Jemmott, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Barbados, 54% of adults approve of hitting children with a belt, cane, or strap ("flogging"), but 74% of Barbadian children oppose flogging or caning at school (Caribbean Development Research Services, 2009). In Jamaica, discipline is severe, consisting of beatings and floggings, and parents use their hands, sticks, belts, shoes and switches to carry out this physical punishment (Burke & Sutherland, 2014). These discipline techniques are not reserved for what would be considered severe infractions; children are punished this way for lying, stealing, being disobedient or impolite; not completing their chores, "playing in the house" "crying too much", and "not eating" the food that was given to them (Smith & Mosby, 2003).…”
Section: Cultural Influences Regarding the Corporal Punishment Of Childrenmentioning
confidence: 99%